Improvement of carotenoids production from Rhodotorula glutinis CCT-2186 - Mussagy, Cassamo Ussemane [UNESP]; Guimarães, Ana Alice Carizia [UNESP]; Rocha, Lara Vicente Ferreira [UNESP]; Winterburn, James; Santos-Ebinuma, Valéria de Carvalho [UNESP]; Pereira, Jorge Fernando Brandão [UNESP] (Elsevier, 2021)
Rhodotorula strains can produce industrial valuable bioproducts. In this work, the production of carotenoids, and lipids by Rhodotorula glutinis using different nitrogen sources was evaluated. Two statistical experimental designs were applied to improve carotenoid production: a first 25−1 fractional factorial design evaluating the influence of independent variables pH, nitrogen source, glucose, KH2PO4 and MgSO4 concentration; a second 22 central factorial design to optimize the effect of pH and nitrogen sources. After the optimization using two statistical designs, a culture mediium composed of (in g/L) glucose (10), asparagine (10), NH4NO3 (4), KH2PO4 (0.52), MgSO4 (0.52) was found as the best for the production of carotenoids at a pH 5 and 30 °C. The best bioprocess was scaled-up to a 5 L stirred-tank bioreactor. The change to a bioreactor allowed to improve aeration and agitation conditions, and consequently, increasing the production yields (m/v) in, approximately, 25.83 %, 11.88 %, 24.50 % and 10.32 % for β-carotene, torularhodin, torulene and lipids, respectively. The combined supplementation of the culture media with both organic (asparagine) and inorganic nitrogen (ammonium nitrate) sources was primordial for enhancing the carotenogenesis. R. glutinis are very efficient in the production of valuable carotenoids and lipids, presenting high potential of yeast for the industrial production of more sustainable cosmetic, pharmaceutical, and food products.
Keywords: Lipids; Production; Rhodotorula glutinis; Torularhodin; Torulene; Yeast; β-carotene